This is my body : I get to choose : an introduction to consent - Turner, Brook Sitgraves (Little Feminist presents series, 2023)
"An anthem for all ages, This is My Body--I Get To Choose features photographs of kids practicing consent out in the real world. Written to help families and educators teach body autonomy and consent, this rhythmic text is a tool for toddlers, preschoolers, and grownups alike"--Back cover.